(untitled) (South East Asia Journal of Public Health, 2015)
Contracting out of health services to the private sectors has been the subject of extensive debate and discussion among health personnel and policymakers. Outsourcing is now considered as a useful management tool for health care managers in the public sector. Outsourcing increases efficiency and service quality, reduces costs, focuses on core processes, improves skills, enhances the overall competitive advantages of the organization, and creates effective occupations in the private sector. The present study aimed to determine the present status of outsourcing hospital services (i.e. radiology, laboratory, nursing, and nutrition) to the private sectors and the propensity of the managers to outsourcing services in six hospitals affiliated to Shiraz University of Medical Sciences, Iran. The study was conducted in six hospitals of Shiraz, Iran in 2012. The study population included all hospitals managers and the sample size was 24. The findings of the study revealed that nutrition, radiology and laboratory services were being outsourced by the hospitals to the private sectors. None of the hospitals outsourced the nursing services. Nutrition service was outsourced by five of the six hospitals, and radiology and laboratory services were outsourced by only one hospital. The highest propensity for outsourcing services among the studied hospital managers were nutrition (87%) followed by laboratory (73.9%), radiology (62.2%) and nursing services (43.3%). Hospital managers and health policy makers should pay more attention to the characteristics of services, besides considering the costs, while outsourcing the services. An effective national policy should be developed to engage the private sectors to improve public health by outsourcing health services. DOI: http://dx.doi.org/10.3329/seajph.v4i1.21843 South East Asia Journal of Public Health Vol.4(1) 2014: 59-62